The Effect of Digital Well-Being and Green Human Resource Management on Work Engagement: Mediating Effect of Change Readiness - Chintya Ones Charli; Mardhatila Fitri Sopali (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Amid rapid organizational changes and digital transformation, understanding what drives employee engagement is crucial. This study investigates the effects of digital well-being and Green Human Resource Management (GHRM) on work engagement, with change readiness serving as an intervening variable. A quantitative study was conducted with 175 private-sector employees in Padang City, analyzed using PLS-SEM. The results indicate that change readiness has a significant positive effect on work engagement, suggesting that employees who are psychologically prepared for organizational change exhibit higher levels of energy, dedication, and work focus. Furthermore, GHRM shows both direct and indirect effects on work engagement, with change readiness acting as a significant mediating mechanism. This finding highlights the role of green HR practices in strengthening employees’ readiness to adapt to change, which subsequently enhances engagement. In contrast, digital well-being does not demonstrate a significant direct or mediated effect on work engagement in this study. The findings emphasize change readiness as a key psychological mechanism linking sustainable HR practices to positive employee outcomes. This study contributes to the literature by demonstrating the importance of GHRM and change readiness in fostering work engagement and provides practical implications for organizations aiming to enhance employee engagement through sustainable HR strategies.